ISLAM DAN TANTANGAN GLOBALISASI Sebuah Pandangan tentang Universalitas Islam I - Imam Tauhid (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2014)
Globalization is a historical fact that has significant influence onsociety’s life system. This condition has to face with wisereaction. Islam as religion that have universal and global order,certainly have role on solving globalization problem. Its clearfrom its universality, Islam can have significant role to shapeglobal community Islamic universalism can be seen from severalmanifestations, e/g: cosmopolitan cultural teaching, sciencedevelopment, holistic social order and complete values.From this, Islam universality is able to face economic, education,culture, technology and other problems.